THE AMPHIBIANS SPECIES IN GUNUNG HALIMUN NATIONAL PARK, WEST JAVA, INDONESIA - Hellen - Kurniati (Masyarakat Zoologi Indonesia, 2006)
Kurniati. H. 2006. The amphibians species in Gunung Halimun National Park,West Java. Zoo Indonesia Vol. 15 (2): 107-120. Five families of frog that exist inJava are represented in Gunung Halimun National Park: the Megophryidae, theBufonidae, the Microhylidae, the Ranidae and the Rhacophoridae. In the park, theBufonidae consists of two subfamilies, the Adenominae and the Bufoninae. TheMicrohylidae only has one subfamily, the Microhylinae, whereas the Ranidae consistsof two subfamilies, the Raninae and the Dicroglossinae. Frog fauna in GunungHalimun National Park is comparatively rich, including 25 species of the 33 species ofnative javan frogs. During herpetofauna survey in October 2001 to August 2002,twenty-five species of amphibian were found in Gunung Halimun National Park; theyconsist of two species of the Megophryidae, five species of the Bufonidae, one speciesTHE AMPHIBIANS SPECIES IN GUNUNG HALIMUN NATIONAL PARK, WEST JAVA,INDONESIA: Zoo Indonesia Vol. 15(2):107 – 120.108of the Microhylidae, twelve species of the Ranidae and five species of theRhacophoridae. Among 33 species of the native javan frogs, eight species areendemic to Java; however six species of the endemic species are inhabited in thepark; they are Leptophryne cruentata, Microhyla achatina, Huia masonii, Nyctyxalusmargaritifer, Philautus vittiger and Rhacophorus javanus.. In Gunung Halimun NationalPark, two major type macro habitats of frog are generally recognized. One major typemacro habitat is primary forest, where Leptobrachium hasseltii, Leptophryneborbonica, L. cruentata, Huia masonii, Rana hosii, Limnonectes microdiscus, N.margaritifer, P. aurifasciatus and P. vittiger are very restricted to this habitat. Anothertype is disturbed habitat, where human has intervened the habitat as secondary forest,degraded forest, cultivation or paddy field. More than half frogs species occur in thesehabitats.